Evaluation of Education Programs in Book Memorization-Based Learning at Madrasah Diniyah Nurul Huda, Kadur District, Pamekasan Regency - Lilik Ernawati; Rusdiana Navlia (Penerbit Presisi Pustaka, 2025)
This article discusses the role of Islamic educational institutions, especially Madrasah Diniyah as a formal institution that plays a crucial role in educating the next generation of Muslims about Islamic principles. The theoretical basis of the definition of madrasah diniyah, the definition of memorization of books, the definition of educational program evaluation and the process of developing students are explained as pillars of understanding. Madrasah Diniyah is known for its development over the years and its contribution to religious education which has received little attention in public schools. This study on Madrasah Diniyah Nurul Huda illustrates how education is carried out using systematic book memorization methods, summative educational evaluation, and religious development that focuses on the morals and social integration of students. Evaluation that highlights the importance of student guardians and the application of tahsin methods to overcome these challenges.In improving academic quality. This article emphasizes that diniyah madrasas are very important for the advancement of Islamic education and the spiritual mental development of the Indonesian nation.